Satisfaction of financial services provided by Touch ‘n Go apps and commercial bank towards Malaysian - Cheong, Sync Yuet; Lee, Jing Ning; Ng, Qian Ning; Pan, Wei Xiong (2023)
This research aims to examine and evaluate the satisfaction of financial services provided by Touch 'n Go apps and commercial banks towards Malaysians. The study employs a primary data collection method, using a Google Form questionnaire targeted at respondents aged between 18 to 25 years old. There are a total of five variables used in the research, including three independent variables (assurance, customer expectation, performance expectancy), one dependent variable (customer satisfaction), and one mediator variable (age). A total of 421 questionnaires were collected, which include 30 pilot test samples and 391 actual samples for further study and data analysis. The data collected was analysed using the SmartPLS analysis software. The research found that only 3 out of 14 hypothesis developments were significant, while the remaining 11 were insignificant. The results show that assurance and customer expectation have a significant impact on the satisfaction of financial services provided by Touch 'n Go, and customer expectation has a significant impact on the satisfaction of financial services provided by commercial banks. However, performance expectancy and age do not significantly impact the satisfaction of financial services provided by commercial banks and Touch 'n Go. Furthermore, the research provides useful data on implications, limitations, and recommendations, providing a useful reference for future research relating to this topic.